1970
DOI: 10.1128/jb.104.1.529-542.1970
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical Localization of Certain Phosphatases in Escherichia coli

Abstract: Cytochemical studies of Escherichia coli at the light and electron microscopic levels have revealed alkaline phosphatase, hexose monophosphatase, and cyclic phosphodiesterase reaction products in the periplasmic space and at the cell surface. In preparations for both light and electron microscopy, reaction product filled polar caplike enlargements of the periplasmic space, such as those described in plasmolyzed cells, indicating significant terminal concentrations of these enzymes; dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

1973
1973
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 48 publications
1
28
0
1
Order By: Relevance
“…Ellar et al (1971) found that glutaraldehyde prevented the selective release of certain enzymes from the cytopl&mic membrane of Micrococcus lysodeikticus. Various concentrations of glutaraldehyde inactivate several periplasmic enzymes (Done et al 1965;Wang & Tu 1969;Wetzel et al 1970), including APase (Wetzel et a! .…”
Section: Interaction With Cell Proteins and Enzymesmentioning
confidence: 99%
“…Ellar et al (1971) found that glutaraldehyde prevented the selective release of certain enzymes from the cytopl&mic membrane of Micrococcus lysodeikticus. Various concentrations of glutaraldehyde inactivate several periplasmic enzymes (Done et al 1965;Wang & Tu 1969;Wetzel et al 1970), including APase (Wetzel et a! .…”
Section: Interaction With Cell Proteins and Enzymesmentioning
confidence: 99%
“…In addition, reaction product for this enzyme has been localized at the fine-structural level in the periplasmic space in other strains of E . coli (26) . taining reaction product for alkaline phosphatase (Fig.…”
Section: Enzyme Localization Within Phagocyticmentioning
confidence: 99%
“…Cluster assembly appears to be a stochastic process involving competition between nucleation of new clusters and growth of existing clusters (Thiem et al, 2007;Thiem and Sourjik, 2008). Similarly, secreted proteins such as alkaline phosphatase or maltose-binding protein collect differentially in the periplasmic spaces of the poles, a phenomenon known as formation of 'polar caps' (Wetzel et al, 1970;Dietzel et al, 1978).…”
Section: Introductionmentioning
confidence: 99%